Current flow dynamics in plasma opening switch - Manuilenko, O.V.; Onishchenko, I.N.; Pashchenko, A.V.; Pashchenko, I.A.; Yuferov, V.B. (Вопросы атомной науки и техники, 2021)
The electromagnetic fields and processes of current flow in the plasma channel of the plasma opening switch were considered in the electron hydrodynamics approximation. Taking into account the nature and features of the current flow through the plasma filled region of plasma opening switch allowed to obtain the structure of the current channel and its dynamics along the plasma. The current flow is a wave process. When this wave reaches the boundary of plasma it seems to be the break of current at this moment. The criterion of this break is obtained. Методами електронної гідродинаміки були розглянуті процеси переносу струму та електромагнітні поля в плазмовій перемичці плазмового комутатора струму. Врахування характеру та особливостей протікання струму по плазмовій перемичці дозволило отримати структуру каналу струму та його динаміку вздовж неї. Протікання струму являє собою хвильовий процес. Розмикання струму пов’язане з досягненням цією хвилею границі плазмової перемички. Отримано критерій розмикання струму. Методами электронной гидродинамики были рассмотрены процессы переноса тока и электромагнитные поля в плазменной перемычке плазменного коммутатора тока. Учет характера и особенностей протекания тока по плазменной перемычке позволил получить структуру канала тока и его динамику вдоль нее. Протекание тока представляет собой волновой процесс. Размыкание тока связано с достижением этой волной границы плазменной перемычки. Получен критерий размыкания тока.